2015
DOI: 10.1186/s12887-015-0406-8
|View full text |Cite
|
Sign up to set email alerts
|

Is there a threshold level of maternal education sufficient to reduce child undernutrition? Evidence from Malawi, Tanzania and Zimbabwe

Abstract: BackgroundMaternal education is strongly associated with young child nutrition outcomes. However, the threshold of the level of maternal education that reduces the level of undernutrition in children is not well established. This paper investigates the level of threshold of maternal education that influences child nutrition outcomes using Demographic and Health Survey data from Malawi (2010), Tanzania (2009–10) and Zimbabwe (2005–06).MethodsThe total number of children (weighted sample) was 4,563 in Malawi; 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
113
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 19 publications
22
113
3
8
Order By: Relevance
“…Although this gradient effect disappeared when adjusting for other independent variables, it merely reflects the fact that maternal illiteracy could contribute not only to wasting but also to other different health related behaviors and problems (Yassin & Lubbad 2010). This result is consistent with the literature that higher levels of maternal education reduced the odds of child wasting (Sengupta et al 2010;Makoka & Masibo 2015). At relatively high levels of maternal education, mothers tend to have acquired the necessary health knowledge and are more able to practice recommended feeding practices for their children (Eunice & Sarah 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although this gradient effect disappeared when adjusting for other independent variables, it merely reflects the fact that maternal illiteracy could contribute not only to wasting but also to other different health related behaviors and problems (Yassin & Lubbad 2010). This result is consistent with the literature that higher levels of maternal education reduced the odds of child wasting (Sengupta et al 2010;Makoka & Masibo 2015). At relatively high levels of maternal education, mothers tend to have acquired the necessary health knowledge and are more able to practice recommended feeding practices for their children (Eunice & Sarah 2013).…”
Section: Discussionsupporting
confidence: 82%
“…At relatively high levels of maternal education, mothers tend to have acquired the necessary health knowledge and are more able to practice recommended feeding practices for their children (Eunice & Sarah 2013). In addition, relatively educated women tend to have relatively fewer children and are able to provide better care and support to their children (Makoka & Masibo 2015), all of which positively impact on children's nutritional outcomes. Socioeconomic status showed that wasting was significantly higher among children of less family income as well as among children who not received nutritional help or donation.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal education can improve child nutrition by increasing income and control of resources in the house. Educated mothers are likely to have better knowledge on child feeding and care and increase access to health and sanitary environment [29,30]. Our result showed that maternal education had negative relationship with stunting.…”
Section: Discussionsupporting
confidence: 50%
“…They are more aware about proper nutrition, maintenance of hygiene, and various health issues as compared to uneducated or less educated women. Earlier studies have also documented the positive impact of mother's education on wasting [31–33]. …”
Section: Discussionmentioning
confidence: 99%